Brain fitness : the easy way of keeping your mind sharp through qigong movements - Kuhn, Aihan (YMAA Publication Center, 2017)
The author shares her expertise in tai chi, qigong, and medicine, emphasizing how tai chi and qigong aid in memory, emotional balance, and lifelong learning. This book features an illustrated manual detailing tai chi and qigong exercises to prevent brain aging; and concise, accessible guidance in combining elements of eastern and western medicine to form a new vision of brain health.--Publisher.